24 - THE BALLROOM DANCE AS A MEANS OF EDUCATION FOR A CULTURE OF PEACE (Fiep Bulletin - online, 2011)
This study aimed to verify, through a questionnaire, the attributes that most contribute to the development of culture of peace through the practice of ballroom dancing. Interference exogenous (environmental, social, economic and emotional) can be viewed as a complex crisis embedded in the intellectual, spiritual and moral values that affect the various social relations between man and the environment in which he lives, affecting their quality of life. Building a culture of peace in any way, it's simple, automatic and fast to be resolved. Therefore, it is valid to recognize that in many segments of contemporary life residing potential for promoting peace, implying that, besides education, as advocated by several studies, the arts can also contribute to its development. In this case, the musicality, for example, dance, singing, the instrument for the assessment, certainly have much to contribute to this purpose. The sample was one hundred and twenty practicing ballroom dancing divided into three groups, three months to six months, up from six months to one year and the third group practicing for over a year, the group was composed of 60% women and 40% of men with a mean age of 48 Â± 12.90 years, practicing ballroom dancing in Rio de Janeiro. Given the results of data collection, it was found that ballroom dancing can be considered as an educational tool in promoting a culture of peace.
Keywords: Ballroom dancing; education; culture of peace